Factors Affecting Debt Policy with Profitability as Moderator - Angelica Valencia; Sherly Lim; Felicia Hanitio; Hasanain Salim Rasheed (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
High levels of corporate debt can impact financial stability and investor confidence, potentially limiting Indonesian non-cyclical consumer companies' capacity for investment and long-term growth. The goal of this research is to analyze the elements influencing debt strategy in non-cyclical companies in the consumer sector that are publicly traded on the Indonesia Stock Exchange from 2021 to 2023, where profitability plays a role as a moderating factor. Purposive sampling was used, with 153 firms represented. This data was analyzed using IBM SPSS 25 with classical assumptions, hypothesis testing, and also moderating regression. Asset structure, institutional ownership, company size, free cash flow, and sales growth are all taken into account. This research utilizes a quantitative method, using moderated regression analysis to investigate how independent variables and debt policy are connected, and how profitability influences these connections. The results indicate that both free cash flow and company size significantly influence debt policy. In contrast, factors like asset structure, institutional ownership, and sales growth appear to have little impact. Furthermore, the moderation test reveals that profitability could be a key factor in shaping the relationship between free cash flow and debt policy. However, profitability cannot offset the impact of asset structure, institutional ownership, firm size, and sales growth on debt policy. These findings suggest that shareholders should monitor firms’ free cash flow and size when evaluating financial risk, while business managers may consider these factors when setting optimal debt levels. Investors can use these indicators to assess a firm's debt capacity and long-term viability.